Analysis of Factors Affecting Poverty in Indonesia - Feronika Zendrato; Paidi Hidayat; Irsad Lubis (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of health, per capita expenditure, population density, labor force, communication expenditure, and inflation on poverty across 34 provinces in Indonesia. The research employs a dynamic panel data method using the Generalized Method of Moments (GMM). The type of data used is secondary data obtained from the Central Bureau of Statistics (Badan Pusat Statistik/BPS) and Bank Indonesia (BI). The independent variables in this study include health, per capita expenditure, population density, labor force, communication expenditure, and inflation, while the dependent variable is poverty. The results indicate that health, per capita expenditure, labor force, and communication expenditure have a negative and significant effect on poverty. Conversely, population density, inflation, and the lag of poverty have a positive and significant effect on poverty in Indonesia.